Caracterización de la Cadena de Abastecimiento de Panela para la Provincia de Bajo Magdalena-Cundinamarca - Orjuela Castro, Javier Arturo; Chavarrio Colmenares, Ivonne Andrea (Ingeniería, 2011)
This paper discusses the most relevant aspects of the production chain of panela (solid sugarcane syrup) and its market in the Province of “Bajo Magdalena” in the department of Cundinamarca, Colombia. These findings are the result of a research project entitled “Integrated Management Model for Food Supply Chain in Bogotá-Cundinamarca “, funded by Colciencias, UESP and the District University, by the Research Group on Industry Competitiveness in Colombian-GICIC. The methodology designed to conduct the research was helpful to achieve the characterization and sizing of the supply chains of panela. It is worth to remark that this methodology might be used to carry out similar investigations in other food chain domains. The results described include the behavior of the production, transformation, commerce, transport and sale point steps in the chain.